(untitled) (Journal of the College of Basic Education, 2023)
Morphological and histological aspects on the cerebellum of( barn owl ) were made in order to find out the cerebellum size, design, lobal, folial variation and the description of the cerebellar regions components at the light microscopical level by using Giemsa stain method . The results of the morphological aspectswere revealed that the cerebellum was large and spade in shape .Sagittal sections revealed the three folded lobes , the arrangement and the nomenclatures of the ten primary folia . The results of the microscopic examinationswere indicated that the three distinct layers of the cortex were more clearly appeared with Giemsa stain methods .The thicker outer light molecular layer were mostly occupied by axons and dendrites . The star shaped stellate cells and the basket cellswere found scattered between them. The single middle purkinje cells layer had large flask shaped cells , the high linear density was in the posterior lobe of the cerebellum . The thick inner dark granular layer had a numerous different neurons,the white matter which formed the medulla was the region of the myelinated fibers and the deep cerebellar nuclei